Pengaruh Capital Intensity dan Good Corporate Governance Terhadap Penghindaran Pajak - Ariyani, Sinta; Sunarto, Sunarto (Universitas Gorontalo, 2024)
This research was conducted with the aim of analysing the impact of capital intensity, institutional ownership, audit quality, audit committee, and independent commissioners on tax avoidance listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The sample that met the criteria in this study was 173 observation data from goods and consumption sector companies listed on the IDX. The data analysis technique in this study uses descriptive statistical analysis, classical assumption test, multiple linear regression test, model testing, and hypothesis testing. The results of this study indicate that capital intensity has a significant positive impact on tax avoidance, institutional ownership has no impact on tax avoidance, audit quality has a significant positive impact on tax avoidance, audit committee and independent commissioners have no impact on tax avoidance.